Role of type I and type III interferons: A review of concepts - Marín Sánchez, Obert (2019)
The interferons (IFN), initially referred to as "soluble mediators that interfere with cell infection by influenza A virus", are families of secreted proteins that regulate innate and acquired immunity after activation of pattern recognition receptors (PRR). The IFN have an impact on the processes of proliferation, differentiation and cell death. The IFN, depending on the molecular characteristics of the gene that encodes it and the target receptors, are divided into three families: type I IFN (IFNα, IFNβ, IFNω, IFNτ, IFNε), type II (IFNγ) and type III (IFNλ1, IFNλ2/3, IFN λ4). In this context, the present article briefly provides important concepts on type I and type III since both share the same signaling cascade; although the mechanism of action of type III IFN, is still little known, these can be used as biological agents compared to type I IFN.